ON SOME RELATIONS CONNECTING FLUID DYNAMICS AND BI-COMPLEX ANALYSIS - Datta, Sanjib Kumar (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In the paper our main target is to derive some results focusing some connection between fluid dynamics and bi-complex analysis which in fact is the most recent mathematical tool to develop the theory of complex analysis. AMS Subject Classification (2010): 30D30,30D35, 76A02. Keywords and Phrases: Potential fluid flow, Â Ïˆ-order (Â Ïˆ-lower order), Ïˆâ€“ zero order (Â Ïˆ-zero lower order),bicomplex number,bicomplex potential, composition, growth indicators, idempotent representation, factorization.